Upaya Menelaah Kembali Konsep Pendidikan Tasawuf Amali di Pondok Pesantren - Wahyudi, Mukhammad (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2020)
Islamic boarding schools provide wider opportunities and stronger currents of transformation which, if not based on spiritual power, can result in embryonic religious education becoming increasingly liberal, materialistic and secular. One way to strengthen the spiritual power of Islamic boarding schools is through practical Sufism education. Moderate Sufistic education that is able to build spiritual and social power as a human responsibility. Therefore, there is a need for a Sufism education concept that can be applied in an amaliah ubudiyah manner, one of which is Amali Sufism, so the focus of this research seeks to find and analyze and get to know amaliah Sufism education in Islamic boarding school institutions holistically. The research method used is literature study, namely the study of literature from various books, journals and other documentation regarding practical Sufism thought. The results obtained are that amali Sufism education prioritizes the applied aspect, so that the Sufism model seems practical and communal, which is the key to building the internalization of Sufism values effectively and efficiently. This concept leads to the moral and moral education of students amidst varied challenges. Thus, ubudiyah charity education can be implemented in a comprehensive, applicable and sustainable manner in cultivating pious attitudes spiritually and socially, so that it has a simple and flexible concept of Sufistic character education. For this reason, the amali Sufism education model is very relevant to the situation and conditions of Islamic boarding schools